Validation of item pool for early adolescents' emotional skills assessment in music therapy - Salokivi Maija; Salanterä Sanna; Saarikallio Suvi; Ala-Ruona Esa (GRIEG ACADEMY, 2025)
Introduction Evaluating the validity of the content is an essential step in developing an assessment tool, including an analysis of the quality of the items within the tool. This study describes the content validation of items in the early adolescents' emotional skills assessment tool in a music therapy context.
Methods Content validity was evaluated based on relevance scores provided by two expert panels. Psychometric scores were obtained by calculating item-specific content validity index (I-CVI), scale-specific content validity index (S-CVI) and modified kappa score. In addition, the coverage and understandability of the items were evaluated.
Results The validation process identified 60 valid items distributed across six components of emotional skills: expressing, monitoring, identifying, understanding, regulating and the ability to use emotional information. Item I-CVI scores ranged from 0.80 to 1.00, the scale content validity index (S-CVI) was 0.95, the modified kappa score ranged from 0.65 to 1.00, item coverage at scale level was 1.00, and item understandability was 0.92.
Discussion The items developed in the study have high validity and are scientifically grounded. The items can be a first step towards a validated assessment tool to evaluate emotional skills in early adolescents. The added value of this study is that the set of items developed is the first to cover all the components of emotional skills identified in the literature. Therefore, music therapists can use the items to observe in more detail the different dimensions of emotional skills in early adolescents.